Exploring postgraduates attitudes towards Grammarly as an automated writing evaluation tool in academic writing - Alghamdi, Arwa Mohammed; AbuSaaleek, Atef Odeh (Studies in English Language and Education, 2025)
Automated writing evaluation (AWE) tools are viral among English as a foreign language (EFL) students in academic writing. Thus, the current study explored EFL postgraduates attitudes toward using Grammarly as an AWE tool in academic writing. Furthermore, the study investigated whether there were significant differences in postgraduates attitudes toward using Grammarly in academic writing based on gender. The study participants were 23 postgraduate students at the English Department of a public university in Saudi Arabia. The study employed a mixed-methods approach to collect data on research design, utilizing both a questionnaire and interview questions. The quantitative data was analyzed using SPSS software, while the qualitative data was analyzed thematically. The findings of the quantitative analysis revealed that the postgraduates had a positive attitude toward using Grammarly in academic writing. The independent t-test resulted in no significant differences among the postgraduates attitudes based on gender. Moreover, based on quantitative and qualitative data analysis, Grammarly provides constructive feedback on students writing as it positively impacts academic writing regarding clarity, accuracy, style, and mechanics. Nonetheless, the results reveal some limitations of using Grammarly, such as incorrect suggestions and an overdependence on AWE tools, which can diminish the writers expression.